Understanding and textual production in students of the first cycle - Salazar Cabrejos, Rosa Eliana (2019)
The comprehension and textual production constitute fundamental axes in the development of the university formation, especially in the subjects of Communication and Language. The difficulties that students present in these processes are due to causes, not only institutional, but also cultural and disciplinary (pedagogy, curriculum and didactics). Processes that demonstrate a communicative competence CC, a knowledge that governs the adequate and correct performance of students as speakers, readers and producers of texts and academic discourses. This competence becomes visible in circumstances in which the professional "exposes", "reads" and "writes" in situations of academic communication. The objective of the research is to analyze-explain the situation of textual comprehension and production of the students of the first cycle of Alas Peruanas University, Chiclayo. The study hypothesis is constructed in the development since the research was exploratorydescriptive. His methodology was developed in a facto-perceptible stage in which text comprehension exercises were applied to identify levels of comprehension and textual production, as well as surveys and documentary analysis guides for curricular documents; the results explain that textual comprehension and production in university higher education is a systematic and organized didactic process, which in the factual reality is disjointed evidence of pedagogical knowledge, curricular plans, didactic acts and disciplinary knowledge. The conclusion ensures the situation comprehension and textual production obeys to disciplinary causes on language (science of language) and educational knowledge on language (pedagogy of language).